INTEGRATION OF AHP AND BMS FOR PRIORITIZING BRIDGE MAINTENANCE IN BEKASI REGENCY - Seftian Setia Pamungkas (Infotronik : Jurnal Teknologi Informasi dan Elektronika, 2026)
Efficient and targeted bridge infrastructure management is a major challenge in Bekasi Regency, given the large number of bridges that have suffered damage due to structural aging, heavy traffic loads, and limited maintenance budgets. This study aims to formulate bridge management priorities based on technical condition and strategic value through the integration of the Bridge Management System (BMS) and the Analytical Hierarchy Process (AHP). The BMS method is used to visually evaluate the physical condition of bridges based on structural parameters. Meanwhile, AHP is applied to assign weights to six priority criteria, namely: bridge condition, daily traffic volume, road connectivity, regional development, role as a connector between economic and agricultural zones, and relationship with public service facilities. The study covers six bridges in Bekasi Regency, with data obtained through field surveys and expert questionnaires. The results of the study indicate that the combination of BMS and AHP produces a priority scale that is more objective, adaptable to the local context, and can be used to formulate more targeted annual budget scenarios. This integrative model is recommended as a decision-making tool for local governments, particularly in the planning and budgeting of future bridge rehabilitation.